Direct thiocarbamation of imidazoheterocycles via dual C–H sulfurization. Issue 34 (13th August 2019) - Deng, Jian-Chao; Zhang, Jun-Rong; Li, Ming-Hua; Huang, Jie-Cheng; Lai, Zhi-Sheng; Tong, Xin-Yu; Cui, Zi-Ning; Tang, Ri-Yuan
Abstract : Direct thiocarbamation via dual C–H sulfurization. Abstract : A copper-catalyzed DTBP oxidative dual C–H sulfurization has been developed for the direct thiocarbamation of imidazopyridines using a combination of elemental sulfur and formamides as carbamothioyl surrogates. NBS (bromo succinimide) was found to promote the thiocarbamation in good yields. This dual C–H sulfurization strategy enables access to a wide range of carbamothioyl imidazoheterocycles without the use of highly toxic phosgene.